Hubungan Permainan Sensorimotor dengan Perkembangan Synaptogenesis pada Anak Usia 5–6 Tahun - Samsu Nurfalah; Salma Rachmah; Sinta Trisnawati; Laili Rahmah (Jurnal Ilmu Pendidikan, 2026)
Early childhood learning still often emphasizes initial academic activities, so play experiences involving body movement and the senses do not always receive adequate space. Children aged 5–6 years need rich, repeated, and meaningful sensorimotor stimulation to support tactile responses, movement coordination, concentration, working memory, and adaptation to new stimuli. This study aimed to determine the relationship between sensorimotor play and synaptogenesis development in children aged 5–6 years at PAUD Darul Iman. This research used a quantitative approach with an associative design. All 20 children in the population were selected as the sample through total sampling. Primary data were collected using a structured observation-based questionnaire completed by parents with teacher confirmation. The instrument used a four-point ordinal Likert-type scale. The results showed that the mean score of sensorimotor play was 20.95, while the mean score of synaptogenesis development was 20.55. All instrument items were valid, with very high reliability for sensorimotor play at 0.952 and synaptogenesis development at 0.951. The normality test showed that the data were not normally distributed, so the hypothesis was tested using Spearman Rank correlation. The test result showed a coefficient of 0.972 with a significance value of <0.001. These findings indicate a positive, very strong, and significant relationship between sensorimotor play and synaptogenesis development as reflected through observable indicators of child development.